Spectroscopic orbits for K giants β Reticuli and ν Octantis: What is causing a low-amplitude radial velocity resonant perturbation in ν Oct? - D. J. Ramm (2018)
New astrometric-spectroscopic orbital solutions for the single-line K-giant binaries β Reticuli (P ≈ 5.2 yr, e = 0.3346 ± 0.0004) and ν Octantis (P ≈ 2.9 yr, e = 0.2358 ± 0.0003) have been derived based on high-precision spectroscopic radial velocities (RVs) and the Hipparcos astrometry. For the case of ν Oct, the simultaneous solution is particularly robust and an inclination of i = 70.8 ± 0.9° has been derived. This is one of the most precise inclinations yet calculated based on a spectroscopic solution and the Hipparcos astrometry. We have also discovered low-amplitude periodic behaviour in the residuals of the orbital solution for ν Oct. This RV perturbation has a semi-amplitude of 50 m s-1and a 418-d period which is coherent over several years. The RV curve of the perturbation is apparently in resonance with that of the binary: every second maximum of the binary coincides with every fifth minimum of the perturbation, hence the periods have the simple ratio 5:2. The possible causes of such a perturbation are rotational modulation of surface phenomenon, pulsations or an orbiting body. We have assessed these alternatives in terms of the suspected photometric stability (Hp= 3.8981 ± 0.0004), a lack of evidence of other RV periodicities, no correlation of cross-correlation function bisectors with the residual velocities, no compelling evidence of wavelength dependency for the amplitude or relative phase of the perturbation, our bounds on the rotational period of the primary star and the need for long-lived relatively fixed surface features. The results of these analyses lack consistency with both rotational modulation and pulsations and so imply that a planetary mass is a realistic cause. The planet hypothesis, however, is strongly constrained and challenged by our precise binary orbit. The hypothetical planet would have an orbit (e ≈ 0.1, a3≈ 1.2 au) about mid-way between the stars whose periastron distance is only 1.9 au. This orbit, supposedly in resonance with the binary system, appears to be highly unlikely based on current planet formation and orbit-stability expectations. Without knowing the cause of the perturbation, we cannot be certain if the suspected RV and hence period resonance are merely coincidental or not. Establishing the true cause of the perturbation requires renewed observation of the system, re-assessment of the possible resonance if this is redetected and the acquisition of similar and additional precise diagnostic parameters with respect to each of the possible causative mechanisms. © 2009 RAS.